The effect of adding radiotherapy to the administrated chemotherapy on infants' gut microbiome - Elsahly, Nourhan (AUC Knowledge Fountain, 2018)
The gut microbiota has been described as the forgotten organ owing to its important roles in the human body, that includes but not limited to: digestion, immunity, homeostasis and response to some drugs such as, chemotherapy and immunotherapy. Its role has been also described in reflection to radiotherapy and associated gastrointestinal injuries, where dysbiosis and its associated side effects could be the driving force for dose determination or the complete suspension of the treatment plan. Linking the gut microbiota alterations to different cancer treatment protocols is not easy, especially in humans. However, enormous effort was exerted to understand this complex relationship. In the current study, we described the gut microbiota dysbiosis in infant sarcoma patients with regards to radiotherapy and antibiotics. Fecal samples were collected as a source of microbial DNA for which the gene encoding for 16S rRNA was sequenced, targeting V3-V5 regions. Two of the three patients understudy had experienced an increase in alpha diversity post treatment. Although phylum Firmicutes overall relative abundance was generally decreasing, six of its taxa increased in all patients. Our results indicate the possibility of radiosensitivity for the elevated taxa. Further studies are needed to describe the extent of radiosensitivity with regards to antibiotic resistance.